The Effect of Word Wall Application on Historical Thinking Ability of History Subject Students in Class XI IPS at SMAN 4 Serang City - Rahmah, Nisa Firdausya; Widodo, Tubagus Umar Syarif Hadi; Fauzan, Rikza (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
This study aims to determine the difference in historical thinking skills between students who use evaluation tools based on word wall applications and students who use written tests, as well as to determine the increase in students' historical thinking skills in history class XI IPS at SMAN 4 Kota Serang after using evaluation tools based on word wall applications. This study uses a type of quantitative research with a quasi-experiment approach method, the sampling technique used is non probability sampling. Data collection in this study using pre-test and post-test. The results of this study show that there are differences in historical thinking skills by obtaining a Sig. (2-tailed) of 0.001 <0.05, which means that there is a significant difference between students who use evaluation tools based on word wall applications and students who use written tests, and there is an increase in students' historical thinking skills by obtaining a Sig. (2-tailed) of 0.000 < 0.05 and tcount = 6.843 > ttable = 1.684 then Ha is accepted and H0 is rejected, which means that there is an increase in students' historical thinking skills in the XI social studies class history subject at SMAN 4 Serang City after using an evaluation tool based on the word wall application.